2020
DOI: 10.1177/1073274820936288
|View full text |Cite
|
Sign up to set email alerts
|

Religious Coping and Quality of Life Among Black and White Men With Prostate Cancer

Abstract: Prostate cancer is a significant impediment in men’s lives as this condition often exacerbates stress and reduces quality of life. Faith can be a resource through which men cope with health crises; however, few studies examine how religion or spirituality can have implications for racial disparities in health outcomes among men. The purpose of this study is to assess the associations between religious coping and quality of life among black and white men with prostate cancer. Data for this investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…Further, religion plays a notable role in the Black communities, rendering the religious institutions essential resources for health care interventions within the Black communities. 25 27 …”
Section: Discussionmentioning
confidence: 99%
“…Further, religion plays a notable role in the Black communities, rendering the religious institutions essential resources for health care interventions within the Black communities. 25 27 …”
Section: Discussionmentioning
confidence: 99%
“…Black men tend to have an earlier onset of chronic diseases, more aggressive disease progression, and more complications than other groups of men. Chronic disease can present multiple stressors including burdensome therapeutic protocols and the loss of income, productivity, and quality of life [21,44]. It has been suggested that religious settings and services present opportunities for individuals to have spiritually enriching experiences and to receive emotional support and affirmative messages useful for coping with the uncertainty, vulnerability, hopelessness, fear, anger, and particularly depression that can accompany chronic conditions [21,26,45].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic disease can present multiple stressors including burdensome therapeutic protocols and the loss of income, productivity, and quality of life [21,44]. It has been suggested that religious settings and services present opportunities for individuals to have spiritually enriching experiences and to receive emotional support and affirmative messages useful for coping with the uncertainty, vulnerability, hopelessness, fear, anger, and particularly depression that can accompany chronic conditions [21,26,45]. Religious institutions can also be sources of social and economic support to obtain important health information and services [9,46,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outrossim, pesquisa realizada nos Estados Unidos com 624 homens com câncer de próstata, evidenciou que o enfrentamento religioso positivo esteve relacionado à melhoria da qualidade de vida 26 , o que salienta que a espiritualidade, religiosidade e crenças pessoais são ferramentas significativas no processo de cura dos pacientes, tendo em vista que por meio da fé gerada por essas facetas são alcançados efeitos benéficos no enfrentamento da doença, na melhora da autoestima, nos sentimentos positivos e no desejo de fazer coisas novas, sendo a dimensão espiritual uma ferramenta inerente aos sujeitos, uma fonte de esperança importante para aliviar o sofrimento e proporcionar maior conforto. 27,28 Quanto às facetas que foram mais bem avaliadas no domínio Relações Sociais encontraram-se a das Relações pessoais (76,22) e Suporte e apoio pessoal (73,77).…”
Section: Homensunclassified